2009
DOI: 10.1093/eurheartj/ehp157
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of CYP2C19 affects both pharmacokinetic and pharmacodynamic responses to clopidogrel but not prasugrel in aspirin-treated patients with coronary artery disease

Abstract: AimsThe metabolic pathways leading to the formation of prasugrel and clopidogrel active metabolites differ. We hypothesized that decreased CYP2C19 activity affects the pharmacokinetic and pharmacodynamic response to clopidogrel but not prasugrel.Methods and resultsNinety-eight patients with coronary artery disease (CAD) taking either clopidogrel 600 mg loading dose (LD)/75 mg maintenance dose (MD) or prasugrel 60 mg LD/10 mg MD were genotyped for variation in six CYP genes. Based on CYP genotype, patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
2
14

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(160 citation statements)
references
References 37 publications
7
128
2
14
Order By: Relevance
“…Common polymorphisms in the CYP2C19 gene, seen in 30-55% of the population depending on the genetic background and ethnic group, significantly diminish response to clopidogrel [50,51]. Clinical studies confirmed the impact of CYP2C19 genotype on clinical outcomes [50,52].…”
Section: Genetic Polymorphismsmentioning
confidence: 86%
“…Common polymorphisms in the CYP2C19 gene, seen in 30-55% of the population depending on the genetic background and ethnic group, significantly diminish response to clopidogrel [50,51]. Clinical studies confirmed the impact of CYP2C19 genotype on clinical outcomes [50,52].…”
Section: Genetic Polymorphismsmentioning
confidence: 86%
“…A significantly lower level of the active metabolite of clopidogrel was found in patients carrying the deficient CYP2C19 gene allele as compared to patients with normal genotype. Such relations were not detected for prasugrel [21].…”
Section: The Role Of Genetic Factors In the Varied Response To Clopidmentioning
confidence: 75%
“…Prasugrel overcame the form of clopidogrel resistance mediated by the CYP2C19*2 variant (Wiviott et al, 2007) which is especially important given that many individuals (25% of Whites, 30% of Africans, and up to 50% of Asians) carry this genetic variant (Mega et al, 2009b). In a randomised study involving 98 aspirin-treated patients with coronary artery disease, it was found that prasugrel efficacy is not dependent on CYP2C19 metabolism when compared to clopidogrel (Varenhorst et al, 2009). Prasugrel also appears to be more effective than clopidogrel in reducing adenosine diphosphate mediated platelet aggregation (Sugidachi et al, 2000;Varenhorst et al, 2009).…”
Section: Clopidigrel Pharmacokineticsmentioning
confidence: 99%
“…In a randomised study involving 98 aspirin-treated patients with coronary artery disease, it was found that prasugrel efficacy is not dependent on CYP2C19 metabolism when compared to clopidogrel (Varenhorst et al, 2009). Prasugrel also appears to be more effective than clopidogrel in reducing adenosine diphosphate mediated platelet aggregation (Sugidachi et al, 2000;Varenhorst et al, 2009). Genetic testing for CYP2C19*2 could assist clinicians in the choice of therapy: carriers of CYP2C19*2 who are unlikely to benefit from clopidogrel should avoid exposure to the drug and be given prasugrel as a safer and more effective alternative.…”
Section: Clopidigrel Pharmacokineticsmentioning
confidence: 99%